History of the Abbasids II (Period of Development and Decline) - Muhammad Yusuf; Nurmalia; Arfandi Setiawan; Suci Fadhilah (Jurnal Pendidikan Islam, 2024)
This research aims to analyze the factors influencing the development and decline of the Abbasid Caliphate during their second period of power. This is a qualitative historical study with a descriptive-analytical approach. Data collection techniques were carried out through a literature review using primary and secondary sources such as books, journals, and historical documents. The data analysis technique involved content analysis to identify the main themes related to the development and decline of the Abbasids. Data validation was conducted through source triangulation to ensure the accuracy and reliability of the information. The results of the study indicate that the development of the Abbasid Caliphate during this period was driven by complex political, economic, and cultural factors, while its decline was triggered by internal conflicts, external attacks, and ineffective administrative issues.